2011
DOI: 10.1186/1743-422x-8-86
|View full text |Cite
|
Sign up to set email alerts
|

Revised cutoff values of ALT and HBV DNA level can better differentiate HBeAg (-) chronic inactive HBV patients from active carriers

Abstract: Background and AimsELISA is still used as primary test for diagnosis HBV disease. However, ELISA-positive patients were marked as HBV inactive after confirmation with PCR and vice versa. Our aim was to assess the performance of new cut-off value of ALT, HBV DNA load and significance of AST as screening tool for HBeAg (-) chronic active or inactive patients in Pakistani population.Materials and methodsIn a cross-sectional, cohort study, 567 HBeAg (-) patients followed for one year were selected. Patients with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 34 publications
(41 reference statements)
0
22
0
Order By: Relevance
“…In a recent study, Kim et al (2011) validated the performance of ALT and HBV DNA, and found that these markers may also be used for discriminating HBeAg (−) active carriers from inactive carriers. In the study by Ijaz et al (2011), HBV DNA load was five times higher in chronic active patients, and a statistically significant positive correlation was found between HBV DNA levels and ALT in HBeAg (−) CHB (r = 0.911, p < 0.05), but no such association was observed for ALT in chronic inactive patients. These studies showed that in HBeAg (−) patients, low HBV DNA levels were associated with less liver damage, although this relationship was not observed in other study (Chan et al 2002).…”
Section: Discussionmentioning
confidence: 90%
“…In a recent study, Kim et al (2011) validated the performance of ALT and HBV DNA, and found that these markers may also be used for discriminating HBeAg (−) active carriers from inactive carriers. In the study by Ijaz et al (2011), HBV DNA load was five times higher in chronic active patients, and a statistically significant positive correlation was found between HBV DNA levels and ALT in HBeAg (−) CHB (r = 0.911, p < 0.05), but no such association was observed for ALT in chronic inactive patients. These studies showed that in HBeAg (−) patients, low HBV DNA levels were associated with less liver damage, although this relationship was not observed in other study (Chan et al 2002).…”
Section: Discussionmentioning
confidence: 90%
“…The cutoff value for serum ALT levels was 40 IU/L and was 35 IU/L for AST [12]. The upper limit of normal for serum AFP levels was ≤10 µg/L [17].…”
Section: Biochemical Tests; Alanine Aminotransferase (Alt or Sgpt) Anmentioning
confidence: 96%
“…The lower limit of detection was 20 IU/mL and the upper limits of detection was 170000000 IU/mL (the quantitative range of this assay is 1.3-8.2 log IU/mL). The Cobas Amplicor HBV Monitor test (real-time polymerase chain reaction, Roche Diagnostic Systems, COBAS® AmpliPrep® HBV Test, COBAS® TaqMan® 48) was used in this study [12,20,21].…”
Section: Serum Hbv Dna Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of advanced fibrosis on noninvasive assessment is an independent predictor of HCC development (7). Although traditional blood tests such as alanine aminotransferase (ALT) levels are useful as measures of disease activity, they have proven poor indicators of liver fibrosis alone (8). Studies in Asia and the United States revealed that 20% to 30% of HBV carriers with persistently normal ALT levels and HBV DNA levels >10 4 copies/mL have stage ≥2 inflammation and stage ≥2 fibrosis on liver biopsy (9).…”
Section: Introductionmentioning
confidence: 99%